Impact of pH on zinc oxide particle size by using sol-gel process - Lee, K. (American Institute of Physics Inc., 2016)
Zinc oxide (ZnO) nanoparticles were prepared and synthesized via sol-gel method, by using citric acid as a precursor. The annealing temperature was fixed at 600Â°C. The impact of pH on the particle size was investigated. Based on the results from the Thermogravimetric Analysis (TGA), three different pH for the precursor which is 3.0, 5.0 and 1.01 were chosen followed by the characterization of the ZnO nanoparticle by using Powder X-Ray Diffraction (PXRD), Transmission Electron Microscopy (TEM) and Field Emission Scanning Electron Microscopy (FESEM). Results showed that the crystallite size estimated from PXRD increased with the pH value which was hexagonal structure for ZnO. TEM further revealed the same tendency which the Zn NPs size also increased with the alkalinity of the precursor. Â© 2016 Author(s).